Rupaning Vrihannala - Listiawan, Ketut Tara; Ruastiti, Ni Made; Suartini, Ni Wayan (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2021)
Rupaning Vrihannala Is A New Dance Creation Based On The Mahabharata In The Story Of Wirataparwa. This Work Is Presented In The Form Of A Duet Dance, By Two Male And Female Dancers, And Is Presented In The Form Of A Freelance Dance With A Performance Structure : Pengawit, Pengawak, Pengecet And Pakaad. This New Dance Creation, Which Was Developed Based On Local Balinese Wisdom, Shows The Love Story Of Arjuna And Dewi Utari During The Panca Pandawa Disguise In The Wirata Kingdom.The Purpose Of This Dance Work Is To Visualize The Truth Values Contained In The Mahabrata Epic, Especially Related To The Wisdom Of Arjuna As A Dance Teacher In The Kingdom Of Wirata. The Admiration For The Wise, Handsome, Good Archery, And Romantic Arjuna Has Inspired The Creation Of This New Dance Creation. The Romance Between Arjuna And Dewi Utari Is Accompanied By Gamelan Gong Kebyar, Supported By Gerong Vocals. This New Dance Creation Was Created Using The Method Of Creating Works Of Art, Which Was Carried Out In Stages, Namely Ngerencana, Nuasen, And Ngebah. All Data That Has Been Collected Through Observation, Interviews, And Literature Studies Were Analyzed Using Art Creation Theory, Symbol Theory, And Imagination Theory. The Process Of Creating This Dance Work Resulted In A New Creation Dance, Rupaning Vrihannala, About The Romance Of Arjuna And Dewi Utari When They Were Disguised As Dance Teachers In The Wirata Kingdom. To Support The Characterizations, Balinese Fashion Make-Up Is Used As A Characteristic, A Symbol Of Local Culture.Keywords: Rupaning Vrihannala, Proses Penciptaan, Struktur Pertunjukan, Tari Kreasi Baru.